MEASURING THE EFFECTIVENESS OF TOURISM MARKETING COMMUNICATIONS MIX IN THE PROVINCE OF LAMPUNG - Muhamad Ariza Eka Eka Yusendra (Saburai International Journal of Social Sciences and Development, 2017)
To promote tourism destinations, the Tourism agency of Lampung Province perform four tourism marketing communications activities, namely: Advertising, Events and Experiences, Words of Mouth, Interactive Direct Marketing. The objective of this study was to measure the effectiveness of every marketing communications mix of tourism in Lampung Province. The analysis method used in this study was EPIC model that measured the effectiveness of marketing communications mix based on four dimensions: Empathy, Persuasion, Impact and Communication. The result showed that the Event and Experience were the most effective marketing communications to promote tourism in Lampung province with the EPIC rate value at 3.65 and categorized effective, while the Advertising and Interactive Direct Marketing were in the category of Effective Enough with the Epic Rate value of each at 2.69, and 3.29. the ineffective communication mix to promote tourism in Lampung province was Words of Mouth with the EPIC rate value of 2.54.